Effects of Land Use and Land Cover Change on Soil Organic Carbon Stock in Jira Watershed, Mid-Lands of Northern Ethiopia. - Assefa, Guesh; Taye, Gebeyehu; Teka, Kassa (Brawijaya University, 2025)
Socioeconomic activities and natural environmental changes are the main drivers of land use and land cover (LULC) changes worldwide and this directly affects the amount of soil organic carbon (SOC) stock. Though LULC affects the amount of SOC stocks and fluxes, the mid-lands of Tigray are less studied and represented. In this study, an attempt has been made to determine the effects of LULC change on SOC at watershed scale in the Central Tigray, Northern mid-lands of Ethiopia. Geographically the study area is found in Kola Tembien district, which is about 125 km away from Mekelle, the capital city of Tigray to the west. Five LULC types (cropland, grazing land, forest land, shrub/bush land and settlement) were identified. Nine composite and undisturbed soil samples at a depth of 20 cm and 10 cm respectively were collected randomly from each LULC type. Analysis of LULC change has been undertaken using satellite images of Landsat 5 TM, Landsat 7 ETM+ and Landsat 8 (OLI) with 30 m spatial resolution in ArcGIS10.3 and ERDAS Imagine14. One-way ANOVA was used for SOC analysis among LULC types. The analysis has showed that LULC change was undertaken in Jira watershed during the last 30 years (1987-2017). The highest SOC concentration was observed in forest land and the lowest was observed in cropland in all studied years. The amount of SOC concentration between each LULC types during all study years was significantly different at p < 0.05 except, cropland and grazing land in 1987 and grazing land and shrub/bush land in all study years. Change in LULC has affected the amount of SOC stock in the LULC types. For example, 18.7 t/ha of SOC was gained during the last 30 years due to the conversion of grazing land into forest land. During the thirty years interval (1987-2017) a total of 714.7 ton of SOC stock was gained due to the conversion of the land uses and management interventions. The highest SOC was gained due to the conversion of grazing land in to forest land (2007-2017) which has offered a total of 635.53 ton of SOC. A model was created to predict SOC of similar environments by using the observed SOC and NDVI values of the 2017 LULC types. Finally, the study concluded that the LULC change has affected the amount of SOC stock in the watershed and it is better to increase coverage of forest lands to store more organic carbon in the soil.